03.01 Adipokines as link between arthritis and metabolism. (1st March 2017) - Hülser, Marie-Lisa; Schreiyäck, Carina; Luo, Yubin; Bozec, Aline; Schett, Georg; MüllerLadner, Ulf; Neumann, Elena
Abstract : Background: The important role of adipokines in obesity and hyperinsulinemia is well characterised. Furthermore, the adipokines adiponectin, visfatin and leptin are known to be immunomodulatory factors in the context of rheumatic diseases. Since hyperinsulinemia and obesity are widespread comorbidities of osteoarthritis (OA), the combination of an OA model (surgical destabilisation of the medial meniscus (DMM)) with hyperinsulinemia and obesity through high-fat diet (HFD) is an obvious consequence. Here we evaluated and correlated systemic vs. local effects of adipokines in OA with normal diet (ND) compared to HFD. Materials and methods: Hyperinsulinemia and obesity in C57Bl/6 mice was induced by HFD containing mainly saturated fatty acids. The control group was fed with ND. Both groups underwent surgical OA induction. Mice were sacrificed 4, 6 and 8 weeks after OA induction. Systemic levels of adiponectin, leptin, visfatin and IL-6 were measured by serum ELISA. Mouse joints were paraffin embedded and stained histologically (H/E, safranin O, pappenheim and Masson-Goldner's trichrome) and local macrophage and adipokine distributions were evaluated by immunohistochemical staining. Results: To exclude acute inflammation as a consequence of the surgery, we confirmed normal levels of IL-6 in all animals. Histological scoring of the mice confirmed OA induction in DMM mice, which was increased when DMM was combined with HFD. Systemic leptin levels were significantly elevated by HFD at all timepoints, but DMM led to a decrease in leptin (3/6 groups significant, e.g. 4 weeks HFD healthy 86.9±17 ng/ml vs. DMM 25.8±15.6 ng/ml). Systemic levels of visfatin, adiponectin and IL-6 did not show strong reactions to diet. Noteworthy, adiponectin was systemically increased by OA induction, but only 8 weeks after surgery (e.g. HFD healthy 6148.65±637.64 ng/ml vs. HFD healthy 5175.95±417.74 ng/ml). Conclusions: OA induced by DMM was aggravated when combined with HFD. Leptin levels in the mouse sera were elevated by HFD but reduced by DMM, which could not be observed for visfatin. Adiponectin seems to play a role in later stages of OA development, since it was solely elevated in later stages of OA. The results show that systemic levels of adipokines can be influenced by DMM and/or HFD.